Effect of Basic Promoters on Porous Supported Alumina Catalysts for Acetins Production - Bezerra, Rita de Cássia F.; Mota, Gabriela; Vidal, Ruth Maria B.; Vitor do Carmo, Jose; Saraiva, Gilberto D.; Campos, Adriana; Oliveira, Alcineia C.; Lang, Rossano; Otubo, Larissa; Jiménez-Jiménez, José; Rodríguez-Castellón, Enrique (IOAP-MDPI, 2022)
A facile strategy for the design of porous supports was obtained by modifying the sol-gel method followed by the wet impregnation technique. In this respect, herein, the acidity of the γ-Al2O3 phase was modulated by adding basic MgO, La2O3 or ZnO promoters to form binary supported catalysts. The Ni and Co dispersion on the supports associated with their tunable acidity and morphologies resulted in highly porous supported alumina-based catalysts. The physicochemical properties of the solids were comprehensively investigated by XRD, textural properties, Raman and FTIR spectroscopy, SEM-EDS, TEM, EPR and XPS analyses. The catalytic performances in the esterification of glycerol in the presence of acetic acid (EG) for the acetins production were evaluated. The highly dispersed NiO and Co3O4 active species on binary porous supports produced synergistic effects appearing to be the reason for the activity of the solids in the EG reaction. Under the optimized reaction conditions, NiCo/MgO-Al2O3 was found to be a robust solid with superior catalytic performance and improved stability in four reaction cycles with 65.0% of glycerol conversion with an exclusive selectivity of 53% for triacetin. The presence of Co2+/Co3+ and Ni2+ strongly interacting with the spinel γ-Al2O3 and MgAl2O4 phases, the latter having a large number of lattice oxygen species, was considered another active component besides those of Ni and Co in the esterification of glycerol.
Keywords: Oxido de aluminio; Porous alumina; Support; Esterification; Glycerol; Basic promoters